2012
DOI: 10.1167/iovs.11-9268
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the Lysyl Oxidase (LOX) Gene Is Associated with Keratoconus in Family-Based and Case-Control Studies

Abstract: Results provided strong genetic evidence that LOX variants lead to increased susceptibility to developing of keratoconus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
102
1
9

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 113 publications
(116 citation statements)
references
References 35 publications
(33 reference statements)
4
102
1
9
Order By: Relevance
“…8 The main statistics used here (allelic test) implicitly assume codominance, and is similar to the additive models assumed in the previous reports. 8,9,13,15 Although some caution is invited in the interpretation of our findings because of the relatively small sample size, the validation of rs2956540:G4C and rs3735520:G4A showing the same effect directions as previous studies in populations of European ancestry adds weight to the existing evidence. 8,9 Although not reaching a statistically significant threshold, the higher MAF of rs1800449:C4T and rs10519694:C4T in controls compared with the KC cases in our study, was consistent with protective effects of these alleles reported in another study using Caucasian case-control panels (Supplementary Table 2).…”
Section: Discussionsupporting
confidence: 48%
See 4 more Smart Citations
“…8 The main statistics used here (allelic test) implicitly assume codominance, and is similar to the additive models assumed in the previous reports. 8,9,13,15 Although some caution is invited in the interpretation of our findings because of the relatively small sample size, the validation of rs2956540:G4C and rs3735520:G4A showing the same effect directions as previous studies in populations of European ancestry adds weight to the existing evidence. 8,9 Although not reaching a statistically significant threshold, the higher MAF of rs1800449:C4T and rs10519694:C4T in controls compared with the KC cases in our study, was consistent with protective effects of these alleles reported in another study using Caucasian case-control panels (Supplementary Table 2).…”
Section: Discussionsupporting
confidence: 48%
“…8,9,13,15 Although some caution is invited in the interpretation of our findings because of the relatively small sample size, the validation of rs2956540:G4C and rs3735520:G4A showing the same effect directions as previous studies in populations of European ancestry adds weight to the existing evidence. 8,9 Although not reaching a statistically significant threshold, the higher MAF of rs1800449:C4T and rs10519694:C4T in controls compared with the KC cases in our study, was consistent with protective effects of these alleles reported in another study using Caucasian case-control panels (Supplementary Table 2). 9 rs1014091:G4A and rs17501108:G4T were previously also shown to have a protective effect, 8 whereas in our study their MAF was higher in KC cases that, albeit not statistically significant, indicated a tendency towards the opposite direction of the effect.…”
Section: Discussionsupporting
confidence: 48%
See 3 more Smart Citations